MONITORING OF DDT IN SOILS NEAR FORMER STOREHOUSES IN THE TALGAR REGION OF THE ALMATY OBLAST (Eurasian Journal of Ecology, 2025)
The main aim of this research was to study soils from five villages located near former warehouses of banned and obsolete pesticides to determine their contents of DDT and its metabolite. Superficial soils were sampled from five villages (Kyzylkairat, Beskainar, Belbulak, Amankeldy and Yenbekshi) in the Talgar region (Almaty oblast) and their contents of organochlorine pesticides were investigated. Physical and chemicals parameters of soils were determined including dry matter, water content, ash, organic matter and pH. Monitoring of soil samples were performed by gas chromatography mass-spectrometry (GC-MS). Beskainar and Kyzylkairat agricultural soils exceeded MRLs for DDTs according to regulations in Kazakhstan, Russia and EU by more than 200 times. The concentrations of DDT found in the other studied soils showed medium levels respecting normative regulations. Nevertheless, concentrations tended to increase in comparison to previously published data of these places.Key words: soil, organochlorine pesticides, monitoring, DUST, DDT, contamination